The Effect of Aerobic Training on Serum Levels of Adiponectin, Hypothalamic-Pituitary-Gonadal Axis and Sperm Quality in Diabetic Rats - Parastesh, Mohammad; Saremi, Abbas; Ahmadi, Akbar; Kaviani, Mojtaba (Urology Journal, 2019)
Purpose: The present study aims to investigate the effects of aerobic training on adiponectin, sex hormones, and sperm parameters in Streptozotocin–Nicotinamide induced diabetic rats. Material and Methods: In the experiment, 52 eight-week-old Sprague Dawley rats (200-250 g) were randomly assigned into three groups: healthy control, diabetic control, and diabetic aerobic training. Diabetes was induced by intraperitoneal injection of nicotinamide solution and STZ solution. The aerobic training protocol was performed for ten weeks. Finally, blood serum was used to assess FSH, LH, testosterone and adiponectin levels. Data were analyzed using ANOVA and Tukey's post hoc test using SPSS-22 software at 0.05 level of significance. Results: Results showed an increase in serum adiponectin levels in aerobic training group, which let to a significant difference between aerobic training group and diabetic control group (3.8±1.1 ?vs 1.6±0.6, P = .42). In addition, aerobic training caused significant increases in serum testosterone level and LH in diabetic aerobic training group, so that significant differences were observed between serum testosterone (5.7±2.3 vs 6.6±1.8, P = .117), LH (4.7±1 vs 5.6±2.8, P = .746) and FSH (5.9±5 vs 4.4±1, P = .596) of diabetic aerobic training group and healthy control group. Sperm parameters in the diabetic aerobic training group including sperm count (26±13.2 vs 11.7±5.7, P = .03, motility (40±6.5%vs 32.5±1.1%, P = .41) and viability (41.7±7.2% vs 29.78±16.2%, P = .000) presented significant differences compared to diabetic control group. Conclusion: Short term aerobic training can improve serum adiponectin levels and sperm parameters, including sperm count and sperm motility through increasing serum testosterone, LH and FSH levels in type 2 diabetic rats.